The effect of the different restorations on fracture resistance of root-filled premolars - Hakan Göktürk; Emine Şirin Karaarslan; Elif Tekin; Bilal Hologlu; Işıl Sarıkaya (BMC, 2018)
Abstract Background The study investigated the fracture resistance of root-filled maxillary premolars with class II cavities restored by different restorations. Methods A total of 55 intact maxillary premolar teeth were included (n = 11). G1 as positive control group, 44 teeth underwent root canal treatment, and MOD cavities were prepared. (G2) no restoration, (G3) direct composite restoration, (G4) direct composite strengthened with buccal to lingual pre-impregnated glass-fibers and (G5) ceramic inlay restoration. After thermocycling, fracture resistance test was performed and fracture type was recorded. Data were analyzed with one-way ANOVA and Chisquare test. Results The mean fracture resistance was as follows: G1 had the highest fracture resistance, G2 had the lowest (p < 0.05). There were no significant differences between the fracture resistance values of the groups that underwent different restorations (G3, G4, G5) (p > 0.05). According to fracture type, the groups showed similar results (p > 0.05). A significant level of unrestorable fracture was detected in G5 (ceramic inlay) (p < 0.05). Conclusions All of the restoration techniques investigated herein increased the fracture strength of teeth; however, all of these values were lower than the fracture resistance of intact teeth. There were no significant differences between the fracture resistance values of the groups that underwent different restorations.